Pengembangan Aplikasi Mobile Learning Berbasis Augmented Reality Materi Bangun Ruang - Khaerul Anam; Gunawan Wiradharma; Mario Aditya Prasetyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Mobile learning as an alternative to today's adaptive learning services by the development of science and technology offers convenience, speed, flexibility, and attractiveness. In addition, the use of learning media is increasingly diverse and interactive, one of which is currently emerging is the use of augmented reality (AR) technology. It is necessary to develop a mobile learning application based on augmented reality for the material contained in the Mathematics Education II course at the PGSD FKIP Study Program at the Open University so that the material is easy to understand. The formulation of the research problem is how to develop the application. The purpose of this research is to develop to conduct a feasibility test of the application. The benefit of this research is knowing the steps taken in developing the application. The research method used is research and development (R&D) with a quantitative descriptive research approach with a questionnaire as a data collection technique. The stages of research and development are by the theory proposed by Borg & Gall. This research focuses on the application development section which consists of two stages. The first stage is the initial trial to create the content and appearance of the application. The second stage is the feasibility of the application according to language, material, and media experts. The results of this study are the quality and feasibility of a mobile learning application based on augmented reality building materials. Keywords: mobile learning, augmented reality, application, learning media, geometry